"Old age is cruel": The right to die as an ethics for living. (22nd June 2018) - Gandsman, Ari
Abstract : In debates over medically assisted dying right to die activists are often accused of embracing an unbridled neoliberal individualistic ethics that devalue life and reject notions of community and care. Through an ethnographic study of activists in North America and Australia, this article aims to complicate this point of view by showing how they are deeply invested in what it means to act morally in the world vis‐à‐vis their relationships with others and how they envisage this issue within an ethics of care. Although activists are often accused by opponents of delegitimising the ageing process and relying on atomised individual values, in depth interviews with right to die activists reveal complex, ambiguous and contradictory reflections on the ageing process as a dominant source of suffering while defending an ethics of care and life. In the end, this article argues that the right to die paradoxically constitutes an ethics for living.